Tea polyphenols attenuate staurosporine-induced cytotoxicity and apoptosis by modulating BDNF-TrkB/Akt and Erk1/2 signaling axis in hippocampal neurons. (June 2020) - Yang, Jian-Rong; Ren, Teng-Teng; Lan, Rongfeng; Qin, Xiao-Yan
Abstract: Tea polyphenols (TP) are the major ingredients in tea beverages that display health-benefits including anti-oxidation, anti-inflammation, anti-aging, attenuating blood pressure and deflating. In this study, we investigated the neuroprotective effects of TP to attenuate staurosporine (STS)-induced cytotoxicity. Rat hippocampal neurons were isolated, cultured and incubated with STS to induce neurite collapse and apoptosis, however, the medication of TP eliminated these adverse effects and maintained the morphology of neurons. STS decreased the expression of pro-BDNF, downregulated the TrkB/Akt/Bcl-2 signaling axis and promoted the activation of Erk1/2 and caspase-3. In contrast, TP rescued the expression of pro-BDNF and antagonistically restored the biochemistry of aforementioned signaling effectors. Consistently, the activity of TP can be attenuated by the inhibition of TrkB or Akt by small chemicals K252a and LY294002. Therefore, BDNF-TrkB and Akt signaling axis is essential for TP-mediated neuroprotective effects. In summary, TP showed beneficial effects to protect neurons from exogenous insults such as STS-induced neural cytotoxicity and cell death.